Forensic Linguistic Analysis of Defamation in Everyday Life - Ndatyapo, Ndamononghenda Ndalipo; Abdulkarimli, Zulgadda; Aihua, Yan; Basa, Rowela (Journal of Language, Literature, and Educational Research, 2024)
Purpose of the study: This study integrates forensic linguistic analysis of word choices, sentence structure, and pragmatic context in both direct and digital communication to explore defamation cases. It examines the motives, impacts, and dynamics of language in such cases through interviews with victims, perpetrators, legal experts, and document analysis. The study connects forensic linguistics with law and communication ethics to foster cross-disciplinary understanding and offer practical guidelines for handling and preventing defamation, while promoting responsible communication. Methodology: Using a qualitative descriptive approach, the study collects data via in-depth interviews, direct observation, and legal document analysis, including court decisions and police reports. Data analysis involves reduction, categorization of linguistic aspects (word choice, sentence structure, pragmatic context), and interpretation based on forensic linguistics and legal theories, with triangulation for validation. Main Findings: The findings reveal that defamation often involves linguistic elements that can be analyzed for legal processes. Digital media plays a significant role in spreading defamation, highlighting the need for better regulation and education. The impact on victims is multidimensional, affecting psychological, social, and economic aspects. Through forensic linguistic analysis, the study contributes both theoretically and practically to resolving defamation cases fairly and effectively. Novelty/Originality of this study: This research offers a novel, multidisciplinary approach to defamation, analyzing both direct and digital communication. It provides a holistic view of linguistic, legal, and ethical aspects, offering practical solutions for media regulation, ethical communication education, and psychological support for victims.